Interactive Powerpoint Based on Constructivism in Mathematics Subjects for Grade VI Elementary School - Ni Kadek Eka Wahyuningsih; Anak Agung Gede Agung; Didith Pramunditya Ambara (Undiksha Press, 2025)
Mathematics learning still tends to rely on conventional methods and lacks the use of interactive media, leading to low student interest and difficulties in understanding abstract concepts such as GCF and LCM. This study aimed to develop, assess the feasibility, and evaluate the effectiveness of an interactive PowerPoint-based instructional media grounded in constructivist principles. It employed a research and development (R&D) approach using the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The subjects included experts in instructional design, content, media, and 19 sixth-grade students. Data were collected using questionnaires and multiple-choice tests, then analyzed using descriptive quantitative statistics and a one-sample t-test. Results indicated the media was of very high quality (>90% score) based on expert validation and product trials. The t-test showed tcalculated (3.432) > ttable (1.734), meaning H0 was rejected and H1 accepted. In conclusion, the constructivist-based interactive PowerPoint media proved feasible and effective in improving learning outcomes on GCF and LCM topics. It is recommended that teachers adopt similar media to foster more active, contextual, and student-centered learning.